0
$\begingroup$

Given, $$f(x) = \begin{cases} \frac{1}{2a} &,& -a \leqslant x \leqslant a\\ 0 &,& otherwise \\ \end{cases}$$ and $Y=X^2$ , therefore , $y\in [0 , \frac{1}{4a^2}]$.

Then, $$F_Y(y) = P(Y \leqslant y) = P(-\sqrt{y} \leqslant X \leqslant +\sqrt{y} ) $$ $$\Rightarrow F_Y(y) = F_X(X \leqslant +\sqrt{y}) - F_X(X \leqslant -\sqrt{y})$$

On differentiating the above equation, $$\frac{d}{dy}F_Y(y) = \frac{d}{dy} \left[F_X(X \leqslant +\sqrt{y}) - F_X(X \leqslant -\sqrt{y}) \right]$$

$$\Rightarrow f_Y(y) = \left(\frac{1}{2\sqrt{y}} \right). \left(f_X(\sqrt{y}) - f_X(-\sqrt{y}) \right)$$

What will be the final expression of $f_Y(y)$? I am having difficulty in determining it because as $y\to0$ , $f_Y(y)\to\infty$.

$\endgroup$
1
$\begingroup$

$$\mathbb{P}(Y<y)=\mathbb{P}(-\sqrt{y}<X<\sqrt{y})=\int_{-\sqrt{y}}^{\sqrt{y}}f_X(x)dx$$

If $\sqrt{y}>a$, then $\mathbb{P}(Y<y)=\int_{-a}^{a}f_X(x)dx =1$

If $\sqrt{y}\leq a$, then $\mathbb{P}(Y<y)=\int_{-\sqrt{y}}^{\sqrt{y}}f_X(x)dx =\int_{-\sqrt{y}}^{\sqrt{y}}\frac{1}{2a}dx=\frac{\sqrt{y}}{a}$

Then for the pdf $f_Y(y)=\frac{1}{2a\sqrt{y}}$ for $y\in [0,a^2]$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.